APLIKASI INFORMASI BUDAYA INDONESIA BERBASIS ANDROID (Information Technology and Telematics, 2016)
Abstract- Indonesian culture is the whole national culture, local culture, and culture of foreign origin that has existed in Indonesia before Indonesia's independence. Indonesian culture is one of the cultural property owned by the Indonesian state and widely praised by other countries. With so many tribes and provinces in the territory of Indonesia, it is automatically also a lot of kinds of Indonesian culture such as traditional clothing, traditional cuisine, traditional song in the whole province of Indonesia because of the many tribes in Indonesia is characterized -ciri special. Indonesian culture is reflected in the various aspects of community life in all regions in Indonesia. Each area have the characteristic of different cultures. System development method used in this study is a prototype consisting of analysis, design, create prototypes, evaluation and improvement, results. System design using OOD which consists of the use case diagrams and activity diagrams. Making the program using the Android programming .. The end result of this research is the application of Indonesian culture android based information can be used to display information Indonesian culture consisting of profiles, galleries, song and video culture of Sumatra, Java, Kalimantan, Sulawesi and Yogyakarta Keywords – Indonesian Culture, OOD, Android, Prototype